2001
DOI: 10.1111/j.1095-8649.2001.tb01396.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of coastal Northwest Atlantic herring populations: implications for management

Abstract: Analysis of nine tetranucleotide microsatellite loci for Atlantic herring at five locations in the Northwest Atlantic including the Bras d'Or Lakes shows considerable genetic variation and significant population structure within the Coastal Nova Scotia management component, and among coastal populations and herring collected from Georges Bank. However, results are also consistent with gene flow across the Gulf of Maine. The magnitude of differentiation between the Bras d'Or Lakes sample and all others consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…Maintaining spatial diversity is as important as rebuilding total numbers, because diversity provides resilience to local changes in environment, exploitation and fish behaviour (McPherson et al, 2001). Ichthyoplankton surveys have allowed us to monitor the abundance of newly hatched larvae and thus the spatial dynamics of the spawning biomass of herring.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining spatial diversity is as important as rebuilding total numbers, because diversity provides resilience to local changes in environment, exploitation and fish behaviour (McPherson et al, 2001). Ichthyoplankton surveys have allowed us to monitor the abundance of newly hatched larvae and thus the spatial dynamics of the spawning biomass of herring.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue samples (blood, fin, or muscle) were collected from spawning stage Atlantic herring at ten locations along the Scotian Shelf, in the Bay of Fundy, and in the Gulf of Maine (Figure 1) in 1998(Figure 1) in , 1999(Figure 1) in , and 2000 (Table 1). Analyses of a subset of some of these collections (Bras d'Or Lake, Georges Bank, Devastation Shoal, Eastern Passage, and Three Fathoms Harbour) were previously reported in McPherson et al (2001b) and discussed in relation to the management of intraspecies genetic diversity along the southern coast of Nova Scotia. Herring from the vicinity of Iceland and the Celtic and Baltic Seas were included in the analyses presented here to provide comparisons of differentiation across the species' range.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, rejections of the null hypothesis of no genetic differentiation among small numbers of populations of northeastern (NE) and northwestern (NW) Atlantic herring have been reported (Shaw et al 1999;McPherson et al 2001b). However, the geographic distances encompassed by the ''population'' samples used in most contemporary studies have generally been limited, and the potential for temporal variation among allele frequencies within location-specific samples was not explicitly assessed.…”
mentioning
confidence: 97%
“…Similar to the NE Atlantic populations, herring in the NW Atlantic undergo north-south and inshore-offshore migrations for feeding and reproduction (19), with spawning taking place mostly during spring and autumn (20) from Cape Cod to northern Newfoundland (14). Previous genetic studies based on a small number of microsatellite markers reported weak but significant genetic structuring between NW and NE Atlantic populations as well as among spawning aggregations within the NW Atlantic (21,22).…”
Section: Significancementioning
confidence: 99%